DIPLOMASI BUDAYA MELALUI FILM DAN KOMIK CAPTAIN AMERICA DALAM MENAIKAN CITRA AMERIKA SERIKAT SEBAGAI NEGARA ADIDAYA DI DUNIA - Hokuto Adijoyo (Jurusan Ilmu Hubungan Internasional, 2018)
This research shows various efforts of culture diplomacy that theUS company—such as Marvel Industry–has made through using movies and comic bookson Captain Americain order to increase the US image as a superpower country. It specifically aims at strengthening American spirit of patriotism and nationalism againstseveral powerful countries,such as Russia and China.Recovering its negative images around the world, the Marvel Industry has sought hard to produced Captain America’s movies and comic books for building new image. The US government indirectly help this effort by issuing policies and various steps for ensuring all steps of producing the movies and comic books have been in line with the ways of increasing the US images internationally.